KOLABORASI TEKNOLOGI DALAM LAYANAN KEUANGAN UNTUK MEMUDAHKAN TRANSAKSI DIGITAL DAN MENCEGAH JUDI ONLINE DI KALANGAN REMAJA SMA NEGERI 7 BANDAR LAMPUNG - Anggraini, Riska; Pratiwi, Yunisa Dwi; Putri, Marcella Wijaya; Andini, Septiyana; Rahmandani, Suci; Rabbani, Muammar Fadhil (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The rapid advancement of digital technology and the widespread access to online financial services have significantly transformed the daily lives of adolescents, particularly in how they conduct financial transactions and interact with digital platforms. While this development offers numerous benefits—such as convenience, speed, and accessibility it also introduces serious challenges, including the rising prevalence of online gambling among teenagers. This study seeks to provide students at SMA Negeri 7 Bandar Lampung with critical education on digital financial literacy and the risks of online gambling. Using a qualitative descriptive approach, the research implements an interactive lecture method supported by group discussions, educational videos, and participatory activities. The program includes three core sessions: introduction to financial technology (fintech), exploration of the negative impacts of online gambling, and a university outreach session. Findings indicate strong student engagement, active participation in discussions, and increased awareness of the importance of self-regulation and digital responsibility.